Pengaruh dari Faktor Sosiodemografi, Pola Makan, dan Klinis terhadap Risiko Retinopati Diabetik pada Pasien Diabetes Tipe 2: Influence of Sociodemographic, Dietary and Clinical Factors on The Risk of Diabetic Retinopathy among Type 2 Diabetic Patients - Dhandapani, Shanthi; Yuvaraj, V.; Narendran, Siddarth; Sharma, Aakriti; Vincy, Catherine Lily; Afshan, Kamar; Premagowri, B.; M, Aruna (Amerta Nutrition, 2025)
Background: Diabetes mellitus is one of the most frequently occurring metabolic disorders, and is associated with Diabetic Retinopathy (DR), which damages the retina and can lead to vision loss. Objectives: The study investigated the relationship between sociodemographic, dietary, and clinical factors on the risk of DR in individuals with Type 2 Diabetes (T2DM). Methods: The study was conducted from November 2023 to April 2024 in Coimbatore, South India. Anthropometric measurements, Demographic, clinical, and dietary details were gathered by interviewing patients. Descriptive and binomial logistic regression were used to find out the relationship between the predictors and DR. Results: A total of 216 patients were diagnosed with T2DM for at least a year, including 41.66% of study participants with retinopathy and 58.33% without retinopathy; the majority (58%) were male, aged 40 to 59. Based on the Multivariable binomial logistic regression, indicated that Occupation (OR: 112.23, 95% CI=6.91,1820), Education (OR: 0.0753,95% CI=0.01,0.53), Monthly income (OR: 0.01,95% CI=0.01,8.27x10-04,0.25), Hypertension  (OR: 1.15,95% CI=0.02,1.89), dry fruits consumption (OR: 11.41, 95% CI=1.009,128.98), sugar and jaggery (OR: 1.10, 95%CI = 0.020,1.521), the monounsaturated oils (Peanut oil, Mustard oil, Sesame oil) (OR: 0.028, 95% CI = 0.037,0.0.22) had significant associations with DR.  Conclusions: Sociodemographic, dietary, and clinical factors appear to have significant associations with the presence and severity of DR. It is important to monitor people with Type II diabetes on a healthy diet, as well as maintaining blood pressure and glycaemic status within the normal range is likely to delay the progression of the disease.